Pediatric Spinal Tumors - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
The clinical outcome and surgical treatment of 34 pediatric spinal tumors seen over an 18-year period (1981-1999) were analysed in a retrospective study at the Neurosurgical University Hospital of Frankfurt am Main, Germany.